Relationship between depressive mood and non-suicidal self-injury in middle school students： the mediating role of impulsivity - Ren Jiangping; He Yan; An Chaodong; Chen Juan (Sichuan jingshen weisheng, 2023)
BackgroundNon-suicidal self-injury （NSSI） behavior poses a significant risk to the psychosomatic health of middle school students. However， the intrinsic mechanisms underlying the risk factors associated with NSSI behavior remain unclear.ObjectiveTo explore the relationship and underlying mechanism between depressive mood， impulsivity， and NSSI behavior in middle school students， and provide valuable insights for the prevention and intervention of NSSI behavior in this population.MethodsIn March 2021， 1 161 middle school students were recruited by cluster random sampling. They were assessed using Adolescent Non-Suicidal Self-Injury Assessment Questionnaire （ANSAQ）， Center for Epidemiologic Studies Depression Scale （CES-D）， and Barratt Impulsivity Scale （BIS-II）. Spearman's correlation analysis was used to examine the correlation between depressive mood， impulsivity and NSSI behavior in middle school students. Moreover， the Process mediation effect analysis was adopted to test the mediating role of impulsivity between depressive mood and NSSI behavior.ResultsTotal of 122 people （10.51%） with NSSI behavior were detected. CES-D score was positively correlated with the total score of BIS-II and scores of all dimensions （r=0.340~0.556， P<0.01）， and also were positively correlated with the total score of ANSAQ and scores of all dimensions （r=0.437~0.540， P<0.01）. Additionally， the total score and dimension scores of BIS-II were positively correlated with the total score and dimension scores of ANSAQ （r=0.157~0.437， P<0.01）. Impulsivity played a partial mediating role between depressive mood and NSSI behavior ［indirect effect=0.035 （95% CI： 0.004~0.067， P<0.01）， indirect effect accounted for 5.81% of the total effect］.ConclusionDepressive mood in middle school students has both a direct and indirect influence on NSSI behavior， partially mediated by impulsivity. Consequently， impulsivity plays a partial mediating role between depressive mood and NSSI behavior.［Funded by Humanities and Social Sciences Research Science Institute of Chongqing Municipal Education Commission （number， 23KSZ017）］